Justification for state intervention in family matters : an analysis from the context of Islamic jurisprudence / Rafeah Saidon ... [et al.] - Saidon, Rafeah; Kamaruddin, Zaleha; Arifin, Mahamad; Ibrahim, Norliah; Sahari, Noorul Huda (Academy of Contemporary Islamic Studies, 2015)
Can the State intervene in family life? Arguments for State intervention in family life usually contend with arguments that emphasise the right of the family to integrity and freedom from State encroachment. Studies have shown that there is a no-end debate on this issue. In view of that, this paper examines the justification of State intervention in family matters from the perspective of Islamic jurisprudence. For this reason, several Shariah principles and rulings are analysed to justify the state intervention and its limitations. As this writing is a conceptual paper, the method used primarily is based on library research, where references comprise extensive literature in the form of books, journal articles, relevant statutes, verses from the Quran and the traditions of the Prophet and his companions. It is found that, being the highest authority entrusted by Allah SWT to sustain the order of the community particularly the family institution, the state has the right to intervene in family matters by imposing both legal and non-legal mechanisms for the purpose of safeguarding the family as intended by Allah SWT. A number of justifications is highlighted in this paper to denote the discretionary power of the State in interfering in the family matters of its citizens.